Revisión documental sobre el impacto de la aplicación del modelo six sigma en pymes colombianas (2018)
In this document a literature review about the implementation of the Six Sigma methodology on national and international level is made, analyzing the impact generated on the enterprises and highlighting the benefits perceived by the same companies. The information gathered can be found in various data bases such as Scopus, Redalyc, Emerald, Google Scholar and EBSCOhost, among others. Starting from this data a bibliometric analysis is made taking into account aspects such as publishing year, subject area, source, affiliation and country of publication, with the purpose of knowing the actual status of the scientific production on Six Sigma implementation, especially on SMEs.